Neascus-type metacercariae in Geophagus brasiliensis (Perciformes: Cichlidae) of Peixe river, Juiz de Fora, Brazil - DOI: 10.4025/actascibiolsci.v30i3.493 - Carvalho, Adriano Reder (2008)
Neascus-type metacercariae, which cause the black spot disease, are described in specimens collected from 33 samples of Geophagus brasiliensis from the Peixe river, in Monte Verde, Juiz de Fora, state of Minas Gerais, Brazil, during March and May 2006. The main morphological features of these metacercariae are: genital primordia composed of three cell masses located in the hind body, and a median dorsal vessel of the reserve bladder around the acetabulum. Thirty fish specimens (90.9%) were parasitized by metacercariae, with mean infection intensity of 15.6 ± 16.1 (1-75). Also, a positive correlation was detected between G. brasiliensis total length and the parasite abundance (r = 0.459; p < 0.01).